2019
DOI: 10.1039/c8nr10238d
|View full text |Cite
|
Sign up to set email alerts
|

Films of filled single-wall carbon nanotubes as a new material for high-performance air-sustainable transparent conductive electrodes operating in a wide spectral range

Abstract: In this paper we show the advantages of transparent high conductive films based on filled single-wall carbon nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 85 publications
2
25
0
Order By: Relevance
“…Thus, the exposed de-bundled SWCNTs are evenly covered with the doping species. Even more, sonication used for dispersion of SWCNTs could facilitate penetration of the dopant species into the inner cavity to fill them [13]. Campo and colleagues reported that the material used in this study can readily accommodate water or hydrocarbons inside of it.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the exposed de-bundled SWCNTs are evenly covered with the doping species. Even more, sonication used for dispersion of SWCNTs could facilitate penetration of the dopant species into the inner cavity to fill them [13]. Campo and colleagues reported that the material used in this study can readily accommodate water or hydrocarbons inside of it.…”
Section: Resultsmentioning
confidence: 96%
“…Regarding the electrical characteristics, similarly to classical semiconductors, surface modification can be exercised on nanocarbon to boost its electrical conductivity via doping [11,12]. Alternatively, the doping species can also be accommodated in the inner cavity of the CNTs [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The observed shift of breathing modes of the LuCl 3 @pSWCNTs, LuBr 3 @pSWCNTs and LuI 3 @pSWCNTs towards higher and lower frequencies as well as the significant changes in the intensity as compared with the pSWCNTs may be associated with a doping effect. [30][31][32][33][34][35][36] The RBM band positions in the spectra of LuI 3 @pSWCNTs are more significantly shifted than those of the LuCl 3 @pSWCNTs and LuBr 3 @pSWCNTs. In addition, the bands that are in resonance via E 11 M transitions present higher shifts in the frequencies, comparing LuX 3 @pSWCNTs (X = Cl, Br, I) with pSWCNTs, because the metallic tubes are more sensitive to doping.…”
Section: Filling and Washing Of Arc-discharge Swcntsmentioning
confidence: 99%
“…The G-band frequency shifts observed between pSWCNTs and LuX 3 @pSWCNTs (X = Cl, Br, I) can be attributed to doping effects, as we already mentioned in the analyses of the RBM. [30][31][32][33][34][35][36] Comparing the spectra of the pristine and filled samples, a weak shift of the G-band to both higher (blueshift) and lower (redshift) frequencies was observed. The contribution of Gmetallic is the most shifted one because it is more sensitive to doping.…”
Section: Filling and Washing Of Arc-discharge Swcntsmentioning
confidence: 99%
“…Therefore, a critical issue is the robust (n, m) identification for individual CNTs to perform statistical analysis of experimental samples. This is particularly important for potential applications such as transparent conductive films 6,7 and transistors 8,9 . Recently, elec-tronic circuits with hundreds of CNT-based transistors 10 and even general purpose CPUs functioning solely with CNT transistors have been produced 11 .…”
Section: Introductionmentioning
confidence: 99%